(untitled) (Rainbow Journal, 2019)
Ethno-medical analysis focuses on cultural systems of healing and the cognitive parameters of illness. It is a traditional non western subject matter of anthropology about the medical knowledge of tribal, peasant and other pre-industrial people. This study is the overview of Nepal based on the ethnographic fieldwork in the Hyolmo community of Melamchi Ghyang, Sindhupalchok aiming to investigate the ethno-medical practices prevalent in the community. Information was gathered by using a number of data-collection techniques like key informants interview, focus group discussion and participant observation. Necessary information was collected through observation examining locale’s ethno-medical practices. Gathered data were thematically analyzed and interpreted. Herbal practices and faith healing is very common in Nepali rural areas whereas Ayurveda, homeopathy Unani etc. are very rarely practiced and almost no practice among Hyolmos. Due to the establishment of health post and availability of medicine, young and educated people have more interest in allopathy. Thus along with the touch with modern world, ethno-medical practices are decreasing.